Pediatric tubular pulmonary heart valve from decellularized engineered tissue tubes. (September 2015) - Reimer, Jay M.; Syedain, Zeeshan H.; Haynie, Bee H.T.; Tranquillo, Robert T.
Abstract: Pediatric patients account for a small portion of the heart valve replacements performed, but a pediatric pulmonary valve replacement with growth potential remains an unmet clinical need. Herein we report the first tubular heart valve made from two decellularized, engineered tissue tubes attached with absorbable sutures, which can meet this need, in principle. Engineered tissue tubes were fabricated by allowing ovine dermal fibroblasts to replace a sacrificial fibrin gel with an aligned, cell-produced collagenous matrix, which was subsequently decellularized. Previously, these engineered tubes became extensively recellularized following implantation into the sheep femoral artery. Thus, a tubular valve made from these tubes may be amenable to recellularization and, ideally, somatic growth. The suture line pattern generated three equi-spaced leaflets in the inner tube, which collapsed inward when exposed to back pressure, per tubular valve design. Valve testing was performed in a pulse duplicator system equipped with a secondary flow loop to allow for root distention. All tissue-engineered valves exhibited full leaflet opening and closing, minimal regurgitation (<5%), and low systolic pressure gradients (<2.5 mmHg) under pulmonary conditions. Valve performance was maintained under various trans-root pressure gradients and no tissue damage was evident after 2 million cycles of fatigue testing.